HAK ASASI MANUSIA DALAM INDUSTRI PARIWISATA BERWAWASAN BUDAYA - Surata, I Ketut (Pusat penelitian & Pengabdian Kepada Masyarakat STP Nusa Dua Bali, 2007)
Human Rights paly crucial role in promoting sustainable tourism development. However their implementation in tourism industry has not been widely carried out. This article, therefore, discusses the impotance of understanding human rights concepts and their implementation in the tourism industry.